PENGUKURAN KEPUASAN PENGUNJUNG DAN PEMETAAN LOKASI WISATA PANTAI DI KOTA BATAM - Anggia Arista; Yan Mahesa Damanik (JURNAL REKAYASA SISTEM INDUSTRI, 2021)
Batam is known as an industrial city, in addition to an industrial city, Batam is also known as a city with beach tourism, some beaches that are often visited by tourists are beaches located in the Barelang area. Coastal tourism needs to be mapped to find out the coastal area. The purpose of this study is to make a mapping of coastal tourist areas that are often visited by tourists using a Geographic Information System based on data on the level of tourist satisfaction with the beach using the servsqual method. based on the results of the study, there are three beaches that are frequently visited by tourists, namely Mirota beach, Melayu beach and Vio-vio beach where based on the level of visitor satisfaction for Mirota beach from the five dimensions using the servsqual method are in the satisfied category, for Malay beach there is one dimension in the dissatisfied category is tangible (-1.005), while for Vio-vio beach there are 2 dimensions in the dissatisfied category, namely tangible (-1.014) and empathic (-1.077). for mapping using a geographic information system where on the map of tourist attractions the coast for the Malay coast is indicated by a red triangle, Mirota beach is indicated by a pink triangle and for Vio-vio beach is indicated by a black triangle. With the mapping of coastal tourism is expected to provide information for tourists in knowing the distribution of coastal areas that are often visited.